Exploration of Targeted Anti-Tumor Therapy 2020
DOI: 10.37349/etat.2020.00004
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer genomic biomarkers in the clinical management of patients with metastatic colorectal carcinoma

Abstract: Colorectal carcinoma (CRC) is an heterogeneous disease in which different genetic alterations play a role in its pathogenesis and progression and offer potential for therapeutic intervention. The research on predictive biomarkers in metastatic CRC (mCRC) mainly focused on the identification of biomarkers of response or resistance to anti-epidermal growth factor receptor monoclonal antibodies. In this respect, international guidelines suggest testing mCRC patients only for KRAS, NRAS and BRAF mutations and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 150 publications
(191 reference statements)
0
4
0
Order By: Relevance
“…The somatic mutations detectable in cfDNA could be instrumental in the rational assignment of immunotherapy and assessment of its effectiveness. For CRC, the total number of somatic mutations, also known as tumor mutation burden (TMB), could be one of the parameters to assess the response to immunotherapy [41,42] A high level of TMB (≥20 mutations/Mb) was found to be associated with microsatellite instability (MSI) or mutations in the two DNA polymerases (POLD and POLE) [42,43]. In a phase II trial, ctDNA was shown to be helpful in assessing the variant allele frequencies (VAFs) as a predictive biomarker for the immunotherapy of patients with solid tumors treated with an anti-PD1 agent.…”
Section: Ctdna For the Therapeutic Decisionmentioning
confidence: 99%
“…The somatic mutations detectable in cfDNA could be instrumental in the rational assignment of immunotherapy and assessment of its effectiveness. For CRC, the total number of somatic mutations, also known as tumor mutation burden (TMB), could be one of the parameters to assess the response to immunotherapy [41,42] A high level of TMB (≥20 mutations/Mb) was found to be associated with microsatellite instability (MSI) or mutations in the two DNA polymerases (POLD and POLE) [42,43]. In a phase II trial, ctDNA was shown to be helpful in assessing the variant allele frequencies (VAFs) as a predictive biomarker for the immunotherapy of patients with solid tumors treated with an anti-PD1 agent.…”
Section: Ctdna For the Therapeutic Decisionmentioning
confidence: 99%
“…Cancer onset and evolution typically result from the accumulation of various molecular aberrations comprising genetic and epigenetic alterations. , The identification of genomic, transcriptomic, and epigenomic abnormalities is critical for precision oncology in many cancers, both to establish molecular subtypes and to offer appropriate treatment. Likewise, the RNA mark landscape evolves along with tumor progression and represents a novel source of biomarkers for personalized medicine . To illustrate this principle, our group has recently uncovered “epitranscriptomic signatures” from glioma patients’ cohorts that could be exploited to guide glioma/glioblastoma diagnosis with unmet accuracy .…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the addition of anti-EGFR monoclonal antibodies to first-line polychemotherapy increases the overall response rate (ORR) and prolongs the progression-free survival (PFS) and overall survival (OS), as compared with chemotherapy alone, in metastatic CRC (mCRC) patients who do not carry either KRAS or NRAS mutations [ 3 , 4 , 5 ]. In fact, the presence of RAS mutations leads to constitutive activation of signaling pathways downstream the EGFR, thus leading to primary resistance to EGFR blockade [ 6 ]. The role of BRAF mutations in the resistance to anti-EGFR antibodies is less defined.…”
Section: Introductionmentioning
confidence: 99%